Crowdsourcing Ideas Using Product Prototypes: The Joint Effect of Prototype Enhancement and the Product Design Goal on Idea Novelty - Althuizen, Niek; Chen, Bo (Management Science, 2022)
When soliciting novel product ideas from the “crowd,” companies may opt to show a prototype in order to steer the generation of ideas in the desired direction. On the one hand, the more features the prototype incorporates, the larger the potential for activating relevant knowledge in memory that may serve as a basis for generating novel ideas. On the other hand, it increases the risk of fixation on the incorporated features, which may inhibit the generation of novel ideas. Based on the “dual pathway to creativity” theory, which identifies the depth and breadth of exploration of one’s knowledge base as cognitive pathways to the generation of novel ideas, we argue that the number (and type) of features included in the prototype in combination with the design goal, that is, generating ideas for functional versus aesthetic product improvements, determines whether the positive effects outweigh the negative effects. With a functional design goal, we find that exposure to a prototype with more features leads to more novel ideas as a result of a more thorough exploration of one’s knowledge base. However, with an aesthetic design goal, exposure to a prototype with more features leads to less novel ideas because of a narrower exploration. The latter effect is driven by people’s tendency to consider the whole or gestalt of the prototype when generating aesthetic ideas. This negative effect can, thus, be mitigated by stimulating people to employ a nonholistic, piecemeal thinking style. This paper was accepted by Ashish Arora, entrepreneurship and innovation.